THE IMPACT OF THE POLICY ON GIVING BONUSES BY THE RIAU PROVINCIAL GOVERNMENT TO ATHLETES WITH ACHIEVEMENTS IN 2017-2018 - Agus Supriadi; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Currently in the city of Pekanbaru, there is a shortage of adequate quality human resources in the field of sports, it is necessary to have a bigger role in achieving sports goals. Policies in terms of sports coaching related to the achievements of athletes need to be aligned to improve human resources, where human resources play an important role in advancing an institution, therefore it is necessary to pay attention to human resources. The formulation of the problem taken is how the impact of the policy of giving bonuses by the Riau Provincial Government to outstanding athletes in 2017-2018.The purpose of this study was first to determine the role of the Riau Provincial government in providing bonuses to athletes, to determine whether the provision of these incentives to athletes was in accordance with the athletes' expectations. And lastly, to find out the obstacles faced by the athletes who had planned not to run according to the predetermined target.The research method used is qualitative research. This type of research is descriptive qualitative, the location of this research is Pekanbaru. Data collection techniques by means of observation, interviews and documentation studies. Data analysis techniques by means of data reduction, data presentation and data verification.The results of the study indicate that the impact of the policy of giving bonuses by the Riau Provincial Government to outstanding athletes shows an improvement in the level of enthusiasm of the athletes by means of identifying the goals to be achieved. Strategy of various steps to achieve the desired goal. The strategy is to select and train outstanding athletes to be prepared for national and international events. The inhibiting factors in the policy of giving bonuses to outstanding athletes are the lack of transparency in giving bonuses to athletes and the lack of training facilities and infrastructure.Keywords: Policy Impact, Giving Bonuses, On Athletes with Achievements